PENERIMAAN DIRI DARI KEGAGALAN AKADEMIK PEREMPUAN PERFEKSIONISME - Tresnani, Lia Dwi; Casmini, Casmini (UIR Press, 2021)
This research aims to describe how academic perfectionism women rise from failure. This research uses a qualitative method with a case study approach. The number of participants in this study was four people obtained by purposive sampling technique with the characteristics of middle-aged adult women, the type of perfection in completing academic tasks, had experienced academic failure, and were willing to become research participants. In-depth interviews and observations collect data. This study indicates that educated perfectionist women always try to achieve maximum results io doing academic work. They also always have high targets that must be completed in their academic life. When they experience academic failures, at first, they tend to be sad, but after that, they can get up quickly. That is because they have a good self-concept of achievement, emotional maturity, belief in God's destiny, and a sense of optimism in themselves, and they also get reinforced motivation through social support from close relatives.